Numerical Study of Porous Media Turbulent Combustion in a Recuperative Reactor - Henriquez-Vargas, L; Donoso-Garcia, P (Begell House Inc., 2016)
This paper presents two-dimensional simulations of turbulent porous media combustion of a methane-Air mixture in a recuperative reactor. Transport equations were written in their time-And volume-Averaged form, and a statistical turbulence model k-ϵ was applied to simulate turbulence generation due to the porous matrix. ANSYS FLUENT was used to simulate the prototype reactor, and user-defined-function (UDF) interfaces for extra terms involving turbulence were incorporated into the solver interface. The study includes the production of thermal NOx modeled by the extended Zeldovich mechanism with postprocessing computation. Different values of operational variables for superficial velocity and equivalence ratio that enable stable combustion within the sistem were sought. For gas mixtures, increasing the fuel gas inlet velocity is accompanied by higher peak temperatures and combustion front displacement toward the reactor outlet. The NOx formation rate is favored with increasing temperature level inside the reactor but is only significant when the temperature exceeds 1800 K. Heat recovery through the system heat bridge raises the temperature of the incoming gas mixture, allowing one to extend the lower limit of flammability for a given set of operational variables, superficial velocity, and equivalence ratio. © 2016 by Begell House, Inc.